Recellularization via the bile duct supports functional allogenic and xenogenic cell growth on a decellularized rat liver scaffold. (2nd January 2017) - Hassanein, Wessam; Uluer, Mehmet C.; Langford, John; Woodall, Jhade D.; Cimeno, Arielle; Dhru, Urmil; Werdesheim, Avraham; Harrison, Joshua; Rivera-Pratt, Carlos; Klepfer, Stephen; Khalifeh, Ali; Buckingham, Bryan; et al.
ABSTRACT: Recent years have seen a proliferation of methods leading to successful organ decellularization. In this experiment we examine the feasibility of a decellularized liver construct to support growth of functional multilineage cells. Bio-chamber systems were used to perfuse adult rat livers with 0.1% SDS for 24 hours yielding decellularized liver scaffolds. Initially, we recellularized liver scaffolds using a human tumor cell line (HepG2, introduced via the bile duct). Subsequent studies were performed using either human tumor cells co-cultured with human umbilical vein endothelial cells (HUVECs, introduced via the portal vein) or rat neonatal cell slurry (introduced via the bile duct). Bio-chambers were used to circulate oxygenated growth medium via the portal vein at 37C for 5-7 days. Human HepG2 cells grew readily on the scaffold (n = 20). HepG2 cells co-cultured with HUVECs demonstrated viable human endothelial lining with concurrent hepatocyte growth (n = 10). In the series of neonatal cell slurry infusion (n = 10), distinct foci of neonatal hepatocytes were observed to repopulate the parenchyma of the scaffold. The presence of cholangiocytes was verified by CK-7 positivity. Quantitative albumin measurement from the grafts showed increasing albumin levels after seven days of perfusion. Graft albumin production was higher than that observed in traditional cell culture. This data shows that rat liver scaffolds support human cell ingrowth. The scaffold likewise supported the engraftment and survival of neonatal rat liver cell slurry. Recellularization of liver scaffolds thus presents a promising model for functional liver engineering.